Circularly polarized luminescence of Sm (III) and Eu (III) complexes with chiral ligand (R/S)‐BINAPO. Issue 4 (12th February 2019) - Cotter, Daniel; Dodder, Spencer; Klimkowski, Valentine J.; Hopkins, Todd A.
Abstract: Luminescent lanthanide (III) ions have been exploited for circularly polarized luminescence (CPL) for decades. However, very few of these studies have involved chiral samarium (III) complexes. Complexes are prepared by mixing axial chiral ligands ( R / S ))‐2, 2'‐bis(diphenylphosphoryl)‐1, 1′‐binaphthyl (BINAPO) with europium and samarium Tris (trifluoromethane sulfonate) (Eu (OTf)3 and Sm (OTf)3 ). Luminescence‐based titration shows that the complex formed is Ln(( R / S )‐BINAPO)2 (OTf)3, where Ln = Eu or Sm. The CPL spectra are reported for Eu(( R / S )‐BINAPO)2 (OTf)3 and Sm(( R / S )‐BINAPO)2 (OTf)3 . The sign of the dissymmetry factors, gem, was dependent upon the chirality of the BINAPO ligand, and the magnitudes were relatively large. Of all of the complexes in this study, Sm(( S )‐BINAPO)2 (OTf)3 has the largest gem  = 0.272, which is one of the largest recorded for a chiral Sm 3+ complex. A theoretical three‐dimensional structural model of the complex that is consistent with the experimental observations is developed and refined. This report also shows that ( R / S )‐BINAPO are the only reported ligands where gem (Sm 3+ ) > gem (Eu 3+ ). Abstract :